Sistem Informasi Pencarian Korban Pasca Bencana Berbasis Web pada BNPB Kota Padang - Khairil Hamdi; Imam Gunawan; Arianto Arianto; Yuhefizar Yuhefizar; Budi Sunaryo (Prosiding SISFOTEK, 2019)
Indonesia is one of the countries that often experiencing natural disaster, both because of geological factors and because of human activities. For example, floods or landslides. These kind of disasters also experienced by West Sumatra, especially in the city of Padang. Post-disaster control that had happened in Padang before meet some difficulty in processing data victims. Family has to recognize the identity and characteristics of the victims while there are not enough hints about the location of the disaster. A government agency for Disaster Management (BPBD) made the information system for searching the disaster victims in the Padang City easier for some stakeholder especially the families of the victims to identify their families. Data will be fast and easy to accessed by anyone, especially by family in identifying their missing family members. This system also can provide information about the searching location.